Teams and Results of The Competition (4D Journal of Landscape Architecture and Garden Art, 2013)
35 teams registered on the Budapest site. The number of submitted entries was 26. In accordance with the rules of Europan the jury awarded two Runnerup prizes. One project received a Special mention prize. Two further projects were selected to the second jury round of the competition.
Keywords: competition